UPAYA GURU DALAM MENANGANI KETERTINGGALAN KEMAMPUAN CALISTUNG PADA KELAS V SEKOLAH DASAR - Rinawati, Agnes; Handayani, Arri; Rakhmawati, Dini (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
Basic skills that every student must possess include reading, writing, and arithmetic (calistung). This study aims to describe the efforts made by teachers to address calistung learning delays among fifth-grade students at SD Negeri Lamper Tengah 02. The research employed a descriptive qualitative method, with data collected through interviews. The results revealed that teachers implemented various instructional strategies, such as remedial teaching, the use of engaging learning media, peer tutoring, active collaboration with parents, differentiated instruction, and efforts to build students’ self-confidence. These planned and consistent efforts proved effective in improving students’ calistung abilities. The findings emphasize the crucial role of teachers as facilitators and motivators in the learning process, particularly in addressing challenges in the post-pandemic era.